Implications of ChatGPT implementation on students' understanding level in Pancasila Education subjects - Ismi Adnin; S. Sapriya; R. Rahmat; Abhi Rachma Ramadhan; Karlin Geriun Antonius Manik; Daffa Fakhri Maulana; Aland Aryaguna; Kireida Rona Islam; Muhammad Fajri Mubarok; Tebi Lesmana (Inovasi Kurikulum, 2024)
Learning requires supporting media to achieve the desired goals. The modern era makes technology an inseparable part of human life, including in the learning process in educational units. The technology that is currently developing rapidly is artificial intelligence (Artificial Intelligence), one of which is implemented in the form of the ChatGPT program. Currently, many students use ChatGPT to help them understand the subject matter, supported by the various conveniences offered by this technology. This study aims to provide an argumentative overview of the importance of utilizing technology, especially the ChatGPT program, in improving student understanding. The approach used in this study is qualitative with a descriptive method, which includes data and document analysis through the process of data reduction, data presentation, and drawing conclusions. In this study, the resource persons involved were 36 students in grade XI-4 at SMA Negeri 1 Tanjung Raja. The results of the study showed that the use of ChatGPT significantly helped improve students' understanding in the Pancasila Education subject, as well as supporting the achievement of educational goals such as critical thinking skills, creativity, and independent problem-solving skills. AbstrakPembelajaran membutuhkan media pendukung untuk mencapai tujuan yang diinginkan. Era modern menjadikan teknologi sebagai bagian yang tak terpisahkan dalam kehidupan manusia, termasuk dalam proses pembelajaran di satuan pendidikan. Teknologi yang saat ini berkembang pesat adalah kecerdasan buatan (Artificial Intelligence) yang salah satunya diimplementasikan dalam bentuk program ChatGPT. Saat ini, banyak pelajar menggunakan ChatGPT untuk membantu mereka memahami materi pelajaran, didukung oleh berbagai kemudahan yang ditawarkan oleh teknologi ini. Penelitian ini bertujuan memberikan gambaran argumentatif tentang pentingnya pemanfaatan teknologi, khususnya program ChatGPT, dalam meningkatkan pemahaman peserta didik. Pendekatan yang digunakan dalam penelitian ini adalah kualitatif dengan metode deskriptif, yang melibatkan analisis data dan dokumen melalui proses reduksi data, penyajian data, hingga penarikan kesimpulan. Dalam penelitian ini, narasumber yang dilibatkan adalah peserta didik kelas XI-4, sebanyak 36 orang di SMA Negeri 1 Tanjung Raja. Hasil penelitian menunjukkan bahwa pemanfaatan ChatGPT secara signifikan membantu meningkatkan pemahaman peserta didik dalam mata pelajaran Pendidikan Pancasila, serta mendukung tercapainya tujuan pendidikan seperti kemampuan berpikir kritis, kreatif, dan keterampilan menyelesaikan masalah secara mandiri.Kata Kunci: ChatGPT; pemahaman peserta didik; pendidikan Pancasila